Delimiting citizen participation: how Israeli mayors get the most out of the process. Issue 1 (2nd January 2022) - Dror, Moshe; Zehavi, Amos
ABSTRACT: Citizen Participation (CP) produces instrumental benefits and realises democratic ideals. However, administrators are aware of its administrative and political downsides. This might lead administrators to adopt symbolic forms of CP in which there is little significance to CP's process and outputs. We investigate how mayors think about CP and the ways in which they shape the practice. Based on in-depth interviews with 15 Israeli mayors, this article studies mayoral views of CP and how these inform practice. We find that mayors adopt 'delimited CP', which goes beyond 'symbolic' CP, in allowing for some significant CP even at the planning level. However, at the same time, mayors reduce possible political and administrative costs in four ways: deciding when to convene CP, controlling its agenda, managing ex-ante and ex-post information flows, and retaining exclusive decision-making power. Lessons from the Israeli case could apply to other 'strong mayor' systems that engage in CP.